Pengaruh Good Governance Terhadap Prestasi Kerja Pegawai Di Kantor Kecamatan Majauleng Kabupaten Wajo - Erna Erna; Yuniarni Yuniarni; Yusran Yusran (Journal of Research and Development on Public Policy, 2024)
Good governance is always related to work, especially good quality work. Government organizations are expected to provide good quality work, so that there is good work performance. This type of research uses census research, where research takes all members of the population as respondents (data sources) and uses questionnaires as the main data collection tool. Using a quantitative approach and using descriptive methods to determine the influence of Good Governance on employee work performance at the Majauleng District Office, Wajo Regency. The results of research data analysis on Good Governance and Work Performance show that Good Governance at the Majauleng District Office is in the good category. Likewise with the Job Performance variable which is in the good category. The influence that the Good Governance variable has on Job Performance is in the very strong and positive category and the data is significant. The conclusion from the research results entitled the influence of Good Governance on Job Performance is as follows. Good Governance at the Majauleng District Office, Wajo Regency is in the good category. The work performance of Majauleng District Office Employees in Wajo Regency is in the very good category. The results of data analysis show that the influence provided is a very strong influence with a positive and significant relationship direction